Perinatal consequences of a category 1 caesarean section at term - Sailesh Kumar; Leah Grace; Ristan M Greer (BMJ Open)
Objective To characterise maternal demographics, obstetric risk factors and neonatal outcomes associated with term category 1 caesarean sections (CS).Design and setting and main outcome measures Retrospective study of term singleton pregnancies delivering at a major tertiary unit in Brisbane, Australia. Category 1 CS were defined as one that required a decision-to-delivery time interval of <30 min when there was an immediate threat to the life of a woman or fetus. Neonatal outcomes analysed were gestation at delivery, birth weight, Apgar scores, acidosis at birth, need for resuscitation, admission to neonatal intensive care and neonatal seizures and death.Results A total of 30 719 women delivering at term were included. Of these, 1179 (3.8%) women required a category 1 CS. A further 3527 women underwent non-category 1 CS. Most category 1 CS were performed for non-reassuring fetal status (65.9%, 777/1179). The indications for non-category 1 CS were for failure to progress (46.5%, 1641/3527) and non-reassuring fetal status (19%, 671/3527). Maternal age, body mass index and medical disease did not differ significantly between the two cohorts. Caucasian women were equally as likely to undergo a category 1 CS as a non-category 1 CS, while indigenous women and women of Asian ethnicity were more likely to undergo a category 1 CS. Significantly higher (p<0.001) perinatal complications were seen in the category 1 CS cohort—Apgar scores <7 at 1 min (20.4%, 241/1179 vs 10.7%, 377/3527) and 5 min (5.8%, 68/1179 vs 1.9%, 67/3527), umbilical arterial pH<7.2 (23.7%, 279/1179 vs 9.1%, 321/3527), neonatal resuscitation (59.9%, 706/1179 vs 51.8%, 1828/3527), neonatal intensive care unit admission (9.8%, 116/1179 vs 2.5%, 87/3527) and seizures (0.8%, 10/1179 vs 0.3%, 9/3527), respectively.Conclusions These results demonstrate significantly poorer outcomes associated with term category 1 CS compared with non-category 1 emergency CS.